Amyand's Hernia in a 6-Week-Old Infant: A Delayed Diagnosis. (7th February 2013) - Piedade, Cláudia; Reis Alves, Júlio
Abstract : In Amyand's hernia, the hernia sac contains the appendix. This can be normal and accidentally found during herniotomy or inflamed and present as acute scrotum, although the latter is less frequent. We present a case of a male infant with scrotal abscess resulting from Amyand's hernia, with appendicitis and periappendicular abscess.